Analisis Single Nucleotide Polymorphism (SNP) Gen Laccase-24 (EgLCC24) dalam Ketahanan Kelapa Sawit (Elaeis guineensis Jacq.) terhadap Ganoderma boninense - Nugroho, Syarul; Yuli Rahmadi, Hernawan; Syukur, Muhamad; Widodo, Widodo; Bayuardi Suwarno, Willy; Sri Wening, Sri Wening; Faizah, Rokhana; Diah Setiowati, Retno; Adriwan Siregar, Heri (Pusat Penelitian Kelapa Sawit, 2025)
Ganoderma boninense attack and its rapid spread in oil palm plantations have caused significant economic losses. The use of Ganoderma resistant plant materials can be a solution, but the allelic segregation that occurs causes not all DxP progeny obtained have the nature of resistance to Ganoderma. The role of molecular markers is needed to assist initial selection of Ganoderma resistant DxP progenies in nurseries. This study aims to identify targeted SNP markers from the Laccase-24 gene (EgLCC24), which is thought to play a role in oil palm resistance to Ganoderma. Three oil palm DxP populations were used in this study, namely populations A, B, and C. Ganoderma screening in nurseries was carried out on these three populations to obtain progeny samples with resistant and susceptible phenotypes, which were then further analyzed. The methods used include SNP analysis and the use of SNAP primers for marker development. The SNP differences obtained from this study led to amino acid changes, but did not cause stop codons. The validation results using SNAP primers on the Laccase-24 gene showed that DxP progeny from populations A, B, and C relatively have moderate allele characteristics of Ganoderma resistance.